2020
DOI: 10.3390/ani10071224
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Covering a Visitor Viewing Area Window on the Behaviour of Zoo-Housed Little Penguins (Eudyptula minor)

Abstract: Studies on the effects of visitors on zoo animals have shown mixed findings and as a result, the manner in which visitors affect zoo animals remains unclear for many species, including a rarely studied taxa such as penguins. Penguins are a common zoo-housed species and have been shown to display huddling, vigilance and avoidance towards zoo visitors which can be indicative of fear. Here, we examined the effects of covering one visitor viewing area window, out of four, on little penguin (Eudyptula minor) behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 57 publications
2
39
0
Order By: Relevance
“…Consequently, the present study results are encouraging for both zoos as it suggests the two zoos are providing positive experiences for visitors at the penguin exhibit that may be related to positive visitor attitudes which is important for the overall ethical foundation of zoos (Maple and Perdue, 2013 ; Sherwen et al, 2018 ). However, despite these positive attitudes, there is evidence at both zoos that close visitor contact increases avoidance of visitors in little penguins (Chiew et al, 2019a , 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Consequently, the present study results are encouraging for both zoos as it suggests the two zoos are providing positive experiences for visitors at the penguin exhibit that may be related to positive visitor attitudes which is important for the overall ethical foundation of zoos (Maple and Perdue, 2013 ; Sherwen et al, 2018 ). However, despite these positive attitudes, there is evidence at both zoos that close visitor contact increases avoidance of visitors in little penguins (Chiew et al, 2019a , 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Visitor attitudes were surveyed in conjunction with our experiments that investigated the effects of regulating visitor contact on little penguin behavior at Melbourne and Taronga Zoo (Chiew et al, 2019a , 2020 ). Visitor contact was regulated by making alterations or manipulations to the exhibit which included, a physical barrier placed 2 m from the enclosure at Melbourne Zoo and a visual barrier that obstructed the view between visitors and penguins at a single viewing window at Taronga Zoo (Chiew et al, 2019a , 2020 ). Chiew et al ( 2019a ) found that the close viewing proximity of visitors can be fear-provoking for little penguins at Melbourne Zoo, shown by the increased number of penguins huddling, vigilant, avoiding the visitor viewing area and decreased number of penguins surface swimming.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations